A Forensic Pathology Investigation of Dismembered Domestic Cats: Coyotes or Cults?. Issue 3 (May 2019) - Nation, P. Nick; St. Clair, Colleen Cassady
Dismembered cats ( Felis catus ) have been found in North American schoolyards, parks, walkways, or lawns and sometimes result in local media attention. When a member of the public encounters these cats, they commonly report finding either the cranial or caudal half of a cat in a prominent location. Such findings cause public consternation and pose difficulties to investigators in identifying whether animal abuse has occurred and whether to concentrate resources on the investigation. This report describes necropsy results from 53 cats involved in such instances in the cities of Edmonton and St. Albert, Canada, from 2007 to 2016. We evaluated these results in relation to 2 hypotheses: that the dismembered cats were the result of human activity, or predation and scavenging by coyotes ( Canis latrans ). The main postmortem features were canine tooth wounds in the neck accompanied by tearing of the subcutaneous structures, skin avulsion, broken claws, and removal of internal organs with the colon and intestine attached to and trailing from the carcass. Based on the nature of the lesions, along with other circumstances of the deaths of the cats in this study, we concluded that these dismembered cat remains resulted from coyote predation on living cats and scavenging of the bodies of cats that died of other causes. We offer additional information to assist veterinarians, veterinary pathologists, and civic officials in identifying the probable cause of death for cat carcasses provided by members of the public.